Substance use among Palestinian youth in the West Bank, Palestine: a qualitative investigation - Salwa G. Massad; Mohammed Shaheen; Rita Karam; Ryan Brown; Peter Glick; Sebastian Linnemay; Umaiyeh Khammash (BMC, 2016)
Abstract Background Youth health risk behaviors, including substance use (psychoactive substances including alcohol and illicit drugs), have been the subject of relatively limited study to date in Middle Eastern countries. This study provides insights into the perceived prevalence and patterns of alcohol and drug use among Palestinian youth. Methods The study was based on ten focus groups and 17 individual interviews with youth aged 16-24 years (n = 83), collected as part of the formative phase of a cross-sectional, population representative study of risk taking behaviors among Palestinian youth in the West Bank in 2012. Qualitative analysis was used to code detailed notes of focus groups and interviews. Results Most participants reported that substance use exists, even in socially conservative communities. Almost all participants agreed that alcohol consumption is common and that alcohol is easily available. The top alcoholic drinks referred to by the study participants were vodka, whisky, beer, and wine. Most participants claimed that they drink alcohol to cope with stress, for fun, out of curiosity, to challenge society, and due to the influence of the media. Participants were familiar with illicit drugs and knew of youth who engaged in drug use: marijuana, cocaine, and heroin were mentioned most frequently. Study participants believed that youth use drugs as a result of stress, the Israeli occupation, inadequate parental control, lack of awareness, unhappiness, curiosity, and for entertainment. Many participants were unaware of any local institutions to support youth with substance use problems. Others expressed their distrust of any such institution as they assumed them to be inefficient, profit-driven, and posing the risk of potential breaches of confidentiality. Conclusions Although this study uses a purposive sample, the results suggest that substance use exists among Palestinian youth. Risk behaviors are a concern given inadequate youth-friendly counseling services and the strong cultural constraints on open discussion or education about the impact of high risk behaviors. These barriers to treatment and counseling can exacerbate the health and social consequences of alcohol abuse and illicit drug use.